(untitled) (Journal of the College of Basic Education, 2023)
Objectives: This study was conducted to evaluate the effect of different doses of captopril on renal function test in patient receiving the drug for various periods of time. Subjects and Methods: Fifty three patients taking captopril therapy (12.5 – 150 mg/day) for management of hypertension or congestive heart failure were included in this study from mosul city. Forty eight apparently healthy subjects of matched age and sex were taken as a control group. They were investigated for blood urea and creatinine concentration and creatinine clearance test was evaluated. Results: The study revealed that captopril had significant effect (P<0.05) in elevation of blood urea and creatinine concentrations with long term of treatment. There were significantly negative correlation (P<0.05) between duration of treatment and creatinine clearance levels. In addition, there were significant effect of short and long term treatment (P < 0.05) on blood urea concentration when compared with control group. Conclusions: Captopril had significant effect on renal function tests and that close monitoring of those patients is needed when the drug is given for long time.